Using Modern Learning Approaches in Teaching Basic Didactics of Mathematics in the Mahara E-Portfolio Environment - Mastnak, Adrijana (Revija za elementarno izobraževanje, 2022)
This paper presents an updated version of the implementation of the course Basics of Didactics of Mathematics. The main goals of the modernization were to use ICT tools and modern learning to overcome objective limitations in the implementation of some elements of the teaching process. For this purpose, we created e-portfolios in the Mahara environment. After the course, students were asked to complete a survey questionnaire. It was found that the updated version of the subject led to improved communication between the participants, increased student engagement in the learning process, and increased student awareness of teaching phenomena. We were not successful in increasing the level of reflection to the point where students would move beyond their initial subjective theories of teaching.